QTc Prolongation in Patients on Antipsychotic Drugs - Dawood, Haider N.; Al- Hadithi, Makki Abdul Kader (Journal of the Faculty of Medicine Baghdad, 2013)
Background: There is a recognized association between prolongation of the heart rate corrected QT interval (QTc) and antipsychotic drugs. QTc prolongation may increase the risk of ventricular tachyarrhythmias, especially torsade de pointes, and therefore, sudden cardiac death.Objective: This study assess the effect of antipsychotics and prolongation of the heart rate corrected QT interval (QTC), and QTC prolongation may increase the risk of ventricular tachyarrhythmias, especially torsade de pointes and sudden cardiac death.Results: Abnormal QTc was defined as an interval of more than 440 ms (0.44 second) and was present in 21.7% (43 patients of 198). Benzhexol (-0.333 – 0.051 second), Fluphenazine (-0.046 – 0.671) were robust predictors of QTc lengthening, also the high antipsychotic dose and combination of antipsychotics and antidepressants were associated with higher incidence of QTc lengthening.Methods: QT interval measured in lead II in electrocardiogram for 198 patients with psychiatric at Baghdad Teaching Hospital and AL – Rashad Teaching hospital from July to October 2001. Bazett formula was used in calculation of corrected QT. By application of the chi – square test "×2" to see the association of QTc prolongation with the cigarette smoking, age, sex, heart rate, cardiovascular disease.Conclusion :Antipsychotic drugs cause QTc lengthening in a dose – related manner. Risks are substantially higher for Benzhexol and Fluphenazine. These drugs may therefore confer an increased risk of drugs – induced arrhythmia.